ANALISIS PENDAPATAN USAHA AYAM BROILER DI DESA WATANG PULU KECAMATAN SUPPA KABUPATEN PINRANG - R, Rahmat (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine how the analysis of broiler business income in WatangPulu Village, Suppa District, Pinrang Regency by using analytical techniques. The data analysis used in this study is descriptive statistical analysis, namely by calculating the average income, per percentage, calculating the sample size, and conducting simplification of data and presentation of data using tables. As for data collection techniques used in this study is documentation. and observation The object in this study is descriptive analysis. Data analysis was carried out in this study using quantitative methods. The results of this study showed that the net income of broiler breeders in WatangPulu Sub-district, Pinrang Regency, fluctuated from year to year. High production costs can be determined from farmer receipts for net income in each period